Analysis of the Theory of Planned Behavior on Intention to Buy Halal Food Products - Anita Maulina; Hartono Hartono; Maya Sofiana (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Consciousness in consuming halal food or products is still ignored by Muslims in Indonesia, which is a country with the largest Muslim population in the world, even though it is a must. Even halal food is defined as food that is healthy, clean and hygienic. This study aims to analyze the behavior of consuming halal food using Theory of Planned Behavior (TPB) and to identify how the purchase intention of Muslims in Indonesia, especially in Jakarta, in buying snacks labeled halal. Using probability sampling techniques, out of 200 questionnaires distributed among students in Jakarta, only 152 were returned and only 137 qualified for further analysis. The quantitative method was chosen for this study with the help of the IBM SPSS version 25 application. After going through the process and variables of Religiosity, Subjective Norm and Perceived Behavioral Control simultaneously affected the Intention to Buy Halal Food variable by 42.6% while the remaining 57.4% was affected. by other variables not examined in this study. To the next researcher, they should choose a wider research sample so that the research results can be more generalized. Can add other variables that are not examined in this study for further research.More insight into the Theory of Planned Behavior (TPB) on Intention to Buy Halal Food by using other variables and research objects.